PENGARUH PERBEDAAN GENDER TERHADAP PRESEPSI DAN KEPEMINATAN PEMAKAIAN PERANGKAT KOMPUTERISASI - Yunita Sari (INSTITUT TEKNOLOGI DAN BISNIS INDOBARU NASIONAL, 2016)
The objective of this study is to investigate whether computer attitude influencesperceived usefulness. This study also investigates whether gender influence relation between perceived usefulness and behavioral intention. The subject is of this study is student from three private university or college of Kota Madya Batam, Kepulauan Riau. There are 150 respondents. The result of study support hypothesis of the study of that the computer attitude influence perceived usefulness. This study also support hypothesis that gender influence relation between perceived usefulness and behavioral intention.